2021
DOI: 10.52082/jssm.2021.222
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Exercise as a Modifier of Depressive Symptoms and Self-Perceived Stress Level in Women with Metabolic Syndrome

Abstract: The study aims to determine the impact of low-intensity exercise and psychoeducation on depressive symptoms and self-perceived stress in women with metabolic syndrome (MetS). Seventy-four women (mean age 69.35 ± 7.20) were included in the study. Participants were divided into two groups: those with MetS (n = 33) and those without MetS (n = 41). Subjects participated in low-intensity general-fitness exercise sessions combined with psychoeducation distributed regularly over a 12-week period. Participants complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 40 publications
(37 reference statements)
1
18
0
Order By: Relevance
“…The present study was designed to assess the effectiveness of virtual therapy in older people whose previous group-based multimodal therapeutic programme did not achieve the expected results. Even though such a therapeutic model meets the requirements of the newest recommendations and its effectiveness has been empirically proven [ 5 , 6 ], there are individuals who additionally need individual therapeutic support. VR therapy and telemental health service seems to be particularly promising fields.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study was designed to assess the effectiveness of virtual therapy in older people whose previous group-based multimodal therapeutic programme did not achieve the expected results. Even though such a therapeutic model meets the requirements of the newest recommendations and its effectiveness has been empirically proven [ 5 , 6 ], there are individuals who additionally need individual therapeutic support. VR therapy and telemental health service seems to be particularly promising fields.…”
Section: Discussionmentioning
confidence: 99%
“…However, around 30% of the subjects did not show the expected improvement and required individual therapeutic support [ 5 ]. The study included people who, despite regularly participating in the therapeutic programme for at least three months, did not experience a satisfactory reduction in depression symptoms and anxiety levels.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study demonstrated that low-intensity physical exercise used in a group setting combined with psychoeducation resulted in significant improvements in both depression and stress levels in women with MetS [ 7 ]. Dance intervention may be an effective adjunct therapy to improve mood and physical function in adults [ 8 ].…”
Section: Introductionmentioning
confidence: 99%